1994
DOI: 10.1002/jmv.1890440114
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution of hepatitis C virus infection in Taiwan

Abstract: To investigate the prevalence of genotype distribution of hepatitis C virus (HCV) infection in Taiwan, genotypes were identified in 122 (36 anti-HCV-positive blood donors, 44 anti-HCV-positive aborigines, 28 hemodialysis patients, and 14 patients with chronic liver diseases) of 280 subjects, using polymerase chain reaction by Okamoto's type-specific primer method. Type II was the dominant (66.7%) type among anti-HCV-positive blood donors, followed by type III and type IV with the same percentages (16.7%), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
1
15
2
Order By: Relevance
“…Such a different prevalence of viral strains has been observed in HCV between northern and southern Taiwanese patients in previous studies. 18,19 Furthermore, since our previous study demonstrated the different predominance of HCV genotype infection in the HCV endemic area of southern Taiwan, 20 we surmised that independent SENV-D/H outbreaks occurred in southern and northern Taiwan. When stratifying patients by age, a trend towards increasing prevalence of SENV-D was observed with older age.…”
Section: Discussionmentioning
confidence: 98%
“…Such a different prevalence of viral strains has been observed in HCV between northern and southern Taiwanese patients in previous studies. 18,19 Furthermore, since our previous study demonstrated the different predominance of HCV genotype infection in the HCV endemic area of southern Taiwan, 20 we surmised that independent SENV-D/H outbreaks occurred in southern and northern Taiwan. When stratifying patients by age, a trend towards increasing prevalence of SENV-D was observed with older age.…”
Section: Discussionmentioning
confidence: 98%
“…The geographical distributions of other HCV genotypes were more restricted, including 4a in the Middle East, Egypt and Central Africa, 5a in South Africa and 6a in Southeast Asia . The most prevalent HCV genotype in Taiwan was 1b . However, previous studies were limited to clinical patients with chronic liver diseases, patients with hemodialysis and individuals from HCV‐hyperendemic areas .…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks are often related to contaminated water and improperly prepared or handled food [Foff, 1995]. Taiwan was a hyperendemic area for HAV infection before 1980 [Wu et al, 1980a]. The seroprevalence of HAV antibodies was higher than 90% with most HAV infection occurring during childhood [Wu et al, 1982].…”
Section: Introductionmentioning
confidence: 99%